THE IMPACT OF FUNDING STRUCTURE ON EU BANKING SECTOR STABILITY - Lech Kujawski; Monika Liszewska; Marta Penczar (Polityki Europejskie, Finanse i Marketing)
In our paper, we analyse the impact of funding structure on banking sector stability in EU countries. Our findings show that after the global financial crisis (GFC) there are four main funding models in the EU banking sectors. We document that funding structure is an important factor influencing the banking sector stability. We report that there are also some other banking business model characteristics as well as macroeconomic indicators which have impact on banking sector risk.